Features of existing design concepts of multirotor-type unmanned aerial vehicles and prospects for their development - Kolesnyk, Oleksii; Kolesnyk, Artem; Betin, Denys (Technology audit and production reserves, 2025)
The object of this study is the design of multirotor unmanned aerial vehicles (UAVs). One of the key challenges is the formulation of multirotor UAV design concepts for solving specific practical tasks. Multirotor UAVs have recently experienced significant development both in terms of structural design and overall conceptual approaches. At the same time, the entire set of ideas, technical solutions, and justifications that determine the principles of design, structure, and the main characteristics of a future UAV has not been considered. Developers of multirotor UAVs have not established a comprehensive classification to support scientifically sound design decisions. This represents a challenge in UAV development, and the present study is dedicated to addressing it. An analysis has been carried out of existing UAV design concepts, their on-board equipment, and fields of application, advantages and disadvantages, as well as potential opportunities for improvement. The study employed system and functional-structural analyses. All possible combinations of design variants were explored and compared with existing solutions. An analysis of the characteristics of multirotor UAVs as a distinct class was carried out, and evidence supporting their designation as a separate type was presented. A study was conducted on the design features of five mini-class multirotor UAVs for performing various tasks, as well as four cargo multirotor UAVs from different countries of origin. Their advantages and disadvantages were identified. The characteristics of power components were described (all UAVs are fully electric, using brushless electric motors), as well as propulsion systems. Recommendations for the design of multirotor UAVs were developed. The study provides insights into the design concept of multirotor UAVs, which can be used for the development of advanced models of such UAVs and the improvement of existing ones, and may serve as a topic for a promising direction of scientific research.